Portraits and Challenges of Indonesia's Modest Fashion Industry on the Halal Industry Competition in the World - Yuniastuti, Viviyanti; Pratama, Andrey Achmad (UIN Sunan Gunung Djati Bandung, 2023)
The Muslim population is spread all over the world, and the majority of Indonesia's population is Muslim. The market segmentation for the halal industry, one of which is modest fashion, has a lot of competition globally. This study describes the development and challenges of Indonesia's modest fashion industry in the global halal industry. The research method is qualitative with a descriptive approach, with data collected from reports and related documents. The results show the simple fashion sector score of Indonesia's Global Islamic Economic Indicator increased from 2018 to 2021 and is ranked in the top 10. Similar development trends occurred in competing countries. Indonesia faces many challenges and stiff competition in the modest fashion sector of the halal industry, including accessing financing and international markets, meeting market needs, receiving government support/related policies, implementing technology in marketing, research and development, and setting competitive prices. However, Indonesia's modest fashion sector is growing.